IV Congreso Latinoamericano y Caribeño de Ciencias Sociales - Freire, A.; Lisi, M.; Tsatsanis, E.; Mélany Barragán; Cristina Rivas (2017)
André Freire, Marco Lisi, Emmanouil Tsatsanis, Xavier Coller, Cristina Rivas & Mélany Barragán (Conveners & Chairs), Organização de 3 Painéis sobre «Political representation in Southern Europe and Latin America: Crisis or Continuing Transformation following the Great Recession? » no IV Congreso Latinoamericano y Caribeño de Ciencias Sociales, University of Salamanca, Spain, July, 17-19, 2017, http://www.flacso.es/4to-congreso-latinoamericano-y-caribeno-de-ciencias-sociales